Correction: Deep-bed filters as post-treatment for ozonation in tertiary municipal wastewater treatment: impact of design and operation on treatment goals. Issue 1 (21st December 2020) - Sauter, Daniel; Dąbrowska, Agata; Bloch, Robert; Stapf, Michael; Miehe, Ulf; Sperlich, Alexander; Gnirss, Regina; Wintgens, Thomas
Abstract : Correction for 'Deep-bed filters as post-treatment for ozonation in tertiary municipal wastewater treatment: impact of design and operation on treatment goals' by Daniel Sauter et al., Environ. Sci.: Water Res. Technol., 2021, DOI: ; 10.1039/d0ew00684j .